Advantages of Live Microscope Video for Laboratory and Teaching Applications. Issue 1 (20th December 2016) - Michels, Kristin K.; Michels, Zachary D.; Hotchkiss, Sara C.
Abstract : Core Ideas: Spatial reasoning and penetrative thinking are difficult concepts for students. Videos used in microscopy pedagogy portray dimensionality. Live video enhances student learning in microscopy in directed study and classrooms. Although spatial reasoning and penetrative thinking skills are essential for many disciplines, these concepts are difficult for students to comprehend. In microscopy, traditional educational materials (i.e., photographs) are static. Conversely, video‐based training methods convey dimensionality. We implemented a real‐time digital video imaging system (VIS) in a collegiate‐level directed study environment to assess the efficacy of live video in microscope pedagogy. We subsequently investigated the utility of live microscope videos by surveying 150 undergraduate and continuing education University of Wisconsin‐Madison students in an introductory biology laboratory course that relies on video technology. In directed study, using a VIS effectively increased student learning by actively engaging both instructors and students while collectively viewing live microscope feeds in real time. The live videos conveyed microscopy concepts, reinforced quality microscope techniques, enhanced penetrative thinking and mental rotation skills, and increased student understanding of multi‐dimensional, microscopic specimens. Survey results indicated that early‐career students also benefited from similar technology and helped students understand complex microscopic structures. We conclude that the application of a VIS in directed study and in classroom‐scale introductory laboratory courses enhances student learning of difficult concepts involving spatial reasoning.